2015
DOI: 10.1016/j.cossms.2014.09.003
|View full text |Cite
|
Sign up to set email alerts
|

The role of electronic energy loss in ion beam modification of materials

Abstract: nuclear energy loss 24 Two-temperature model 25 Thermal spike model 26 Ion annealing 27 Synergistic effects 28 2 9 a b s t r a c t 30 The interaction of energetic ions with solids results in energy loss to both atomic nuclei and electrons in 31 the solid. In this article, recent advances in understanding and modeling the additive and competitive 32 effects of nuclear and electronic energy loss on the response of materials to ion irradiation are reviewed. 33 Experimental methods and large-scale atomistic simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
88
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 170 publications
(91 citation statements)
references
References 74 publications
0
88
0
Order By: Relevance
“…We find temperature dependence of the ion track size. We also find a threshold in the electronic energy loss for a given pre-existing defect concentration, which indicates a threshold in the synergy between the inelastic and elastic energy loss.Ó 2015 Acta Materialia Inc. All rights reserved.Electronic effects are of significant importance in a wide variety of fields where high energy irradiation processes take place, including nuclear applications, the semiconductor industry, material synthesis, modification and characterization [1,2]. The importance of the coupling of electronic and atomic processes in ionic and covalent materials has been emphasized in recent studies [3-15,1], where it has been shown that these effects can have linearly additive [3][4][5][6][7][8] or competing [9-11] impacts on the defect production.…”
mentioning
confidence: 99%
“…We find temperature dependence of the ion track size. We also find a threshold in the electronic energy loss for a given pre-existing defect concentration, which indicates a threshold in the synergy between the inelastic and elastic energy loss.Ó 2015 Acta Materialia Inc. All rights reserved.Electronic effects are of significant importance in a wide variety of fields where high energy irradiation processes take place, including nuclear applications, the semiconductor industry, material synthesis, modification and characterization [1,2]. The importance of the coupling of electronic and atomic processes in ionic and covalent materials has been emphasized in recent studies [3-15,1], where it has been shown that these effects can have linearly additive [3][4][5][6][7][8] or competing [9-11] impacts on the defect production.…”
mentioning
confidence: 99%
“…Raman spectroscopy has been increasingly applied for the structural characterization of ion-beam modified materials, such as in carbides [36][37][38] and oxides [39][40][41][42]. More recently, micro-Raman spectroscopy has been used to characterize the damage created over the entire ion range [36,41,42] to provide new information on quantification of the damage and structure modification as a function of depth, and on enlightenment of possible synergistic effects due to both nuclear and electronic energy deposition to the materials [31].…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…Recent advances in RBS and RBS/C include the study of ion beam induced surface and interface engineering [29], of the role of electronic energy loss on ion beam modification of materials [20,22,30,31] and radiation research on ion irradiation damage evolution from cryogenic temperatures to elevated temperatures [28,30]. For example, yttria-stabilized cubic zirconia (YSZ or cZrO 2 ), as a material widely used for electronic, space, and nuclear applications, was irradiated with 4 MeV Au 2+ ions from liquid nitrogen temperature (80 K) to 1073 K. Several characterization techniques, such as RBS/C and XRD (see Section D), were used to monitor the disordering process including defect production, strain buildup, and dislocation formation, and to identify the microstructural changes.…”
Section: Rutherford Backscattering Spectrometrymentioning
confidence: 99%
“…Based on integrated experimental techniques and computational approaches, researchers have studied the separated and coupled response of some ceramic materials to ion energy loss by electronic energy loss (ionization effects) and nuclear energy loss (displacement events). 14,26,38,39 Similar to the focused-ion-beam, an incident e-beam also exhibits ionization and displacement effects on the target materials. In this study, some of the possible mechanisms that may be attributed to the high-power e-beam-induced crystallization are the atomic displacement effect, 40,41 the ionization effect, 19 and the beam-heating effect.…”
Section: -3mentioning
confidence: 99%
“…The role of electronic deposition and the coupled dynamics of electronic and atomic processes need to be studied over a range of irradiation conditions to elucidate the underlying mechanisms for different classes of materials. 26 Lately, the preparation of waste forms on the nanoscale has attracted much attention owing to their enhanced radiation resistance, such as is observed in silicon carbide, 27 pyrochlore Gd 2 30 For the nanocrystalline materials, abundant grain boundaries can act as sinks for the irradiation-induced defects and hinder the accumulation of the defects. 29,31 However, nanocrystalline materials may be more inclined to ion-irradiation-induced amorphization given their very small particle size in which the excess surface energy leads to a more stable amorphous structure.…”
Section: Introductionmentioning
confidence: 99%